Kaizen Perspective in Curriculum Development - Duran, Volkan; Mertol, Hüseyin (Asian Journal of Education and Training, 2020)
Kaizen is the combination of the words kai (change) and zen (better) in Japanese. It means change for the better, continuous improvement (Albayrak, 2019). In Japan, Kaizen is a task for all staff and stakeholders. Kaizen can be regarded as the reflection of two different perspectives on management in terms of two distinct cultures. The difference between these two approaches is that the Western perspective focuses on the result of the premise while Japanese perspective zeroes on the process. While it is aimed to solve the problems by the stakeholders in different positions in terms of Western perspective, it is common to solve them together in Kaizen philosophy. This kind of habit of putting the hand under the stone has brought success in competition for Japan in business and manufacture. Hence, in this study it is aimed to investigate the basic principles of the Kaizen approach in terms of curriculum development and its principles, so the questions given as follows are sought: 1. What are the core principles of the Kaizen approach? 2. How the Kaizen approach is applied in different branches as well as education? 3. What kind of a curriculum development model can be suggested to improve the Kaizen approach in curriculum and development process? Therefore, Kaizen principles will be examined through document analysis technique in order to reveal core principles of it in the context of curriculum development models as well as proposing curriculum development model based on Kaizen approach. It can be inferred that the core principles of the Kaizen approach have many similarities and differences with curriculum and development approaches.